Legal Protection in Sharia Securities-Based Crowdfunding: A Normative Review of Dual Regulation - Noor, Afif; Ghofur, Abdul; Supangat; Fittria, Anis (Al-Manahij: Jurnal Kajian Hukum Islam, 2025)
Sharia Securities-based crowdfunding (Sharia SBC) has emerged as a novel financial innovation that integrates Islamic principles with financial technology, expanding investment access in Indonesia. However, this development has also created significant regulatory gaps and legal risks related to data protection, Sharia compliance, information asymmetry, and weak dispute resolution mechanisms. This study examines the adequacy of Indonesia’s dual regulatory model, the Financial Services Authority (OJK) and the National Sharia Council (DSN-MUI), in protecting investors and ensuring Sharia compliance in SBC. Using normative legal methods combined with comparative and policy-oriented approaches, the study identifies the lack of binding force in DSN-MUI fatwas, the limited role of the Sharia Supervisory Board, and weak enforcement of data security and disclosure standards. Comparative studies from Malaysia and Bahrain suggest that integrating Sharia audits and a centralized dispute resolution mechanism can strengthen legal certainty. These findings underscore the need for regulatory reforms to render DSN-MUI fatwas legally binding, establish a Sharia arbitration body, and mandate annual Sharia compliance audits for SBC operators. These recommendations aim to improve legal certainty, investor protection, and the integrity of Shariabased financial technology in Indonesia.